2022
DOI: 10.3847/1538-4357/ac9e01
|View full text |Cite
|
Sign up to set email alerts
|

The Poor Old Heart of the Milky Way

Abstract: Our Milky Way should host an ancient, metal-poor, and centrally concentrated stellar population, which reflects the star formation and enrichment in the few most massive progenitors that coalesced at high redshift to form the proto-Galaxy. While metal-poor stars are known to reside in the inner few kiloparsecs of our Galaxy, current data do not yet provide a comprehensive picture of such a metal-poor “heart” of the Milky Way. We use information from Gaia Data Release 3, especially the XP spectra, to construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 95 publications
(157 reference statements)
6
66
0
Order By: Relevance
“…Theoretically, our intrinsic scatter measurements provide a target for simulations of galaxy formation that have the resolution to track enrichment and feedback at the individual supernova level and ISM mixing processes at the 10 3 -10 4 M e mass scale. Chemodynamical studies show that the metallicity range spanned by our sample is one over which the Milky Way transitioned from disordered kinematics to a rotationally supported system (Belokurov & Kravtsov 2022;Conroy et al 2022;Rix et al 2022). The detailed abundance patterns of stars across this transition, including the individual element scatter about average trends, will help to reveal how today's Galactic disk emerged from the chaotic environment of the proto-Galaxy.…”
Section: Discussionmentioning
confidence: 89%
“…Theoretically, our intrinsic scatter measurements provide a target for simulations of galaxy formation that have the resolution to track enrichment and feedback at the individual supernova level and ISM mixing processes at the 10 3 -10 4 M e mass scale. Chemodynamical studies show that the metallicity range spanned by our sample is one over which the Milky Way transitioned from disordered kinematics to a rotationally supported system (Belokurov & Kravtsov 2022;Conroy et al 2022;Rix et al 2022). The detailed abundance patterns of stars across this transition, including the individual element scatter about average trends, will help to reveal how today's Galactic disk emerged from the chaotic environment of the proto-Galaxy.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Myeong et al (2022) argued for an in situ origin of Heracles. More recently, this population has been interpreted as the first stars that formed in the MW, based on Gaia, APOGEE DR17, and H3 survey data (Belokurov & Kravtsov 2022;Conroy et al 2022;Rix et al 2022).…”
Section: Comparison With Other Scenariosmentioning
confidence: 99%
“…The spectra are provided for ∼ 220 million stars in Gaia with 𝐺 < 17.65. Despite their low resolution, several studies have demonstrated that the information content is sufficient to measure bulk spectroscopic parameters (𝑇 eff , log 𝑔, [M/H], Liu et al 2012;Witten et al 2022;Xylakis-Dornbusch et al 2022;Andrae et al 2022;Fouesneau et al 2022;Creevey et al 2022;Belokurov et al 2022;Rix et al 2022) although detailed chemical abundances are likely too challenging (Gavel et al 2021). However, particularly in cooler stars, the presence of molecular features in these spectra is detectable (Lucey et al 2022) enabling more accurate metallicity determinations and detailed carbon abundances.…”
Section: Unsupervised Classification Of O-rich/c-rich Long-period Var...mentioning
confidence: 99%